2020
DOI: 10.1016/j.jvolgeores.2018.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Seismic imaging in the Krafla high-temperature geothermal field, NE Iceland, using zero- and far-offset vertical seismic profiling (VSP) data

Abstract: Among geothermal exploration methods, active surface seismic methods have played only a minor role to date. Especially in high-temperature volcanic systems, reflection seismic data often reveal poor delineation of volcanic features, due to the internal heterogeneity of volcanic sequences. To enhance the vertical resolution, one possibility is the application of downhole seismic methods like vertical seismic profiling (VSP). A test experiment was carried out in the Krafla hightemperature geothermal field, NE-Ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Thus, the profiling results [53,54], as well as our results, detected the state of subsurface velocity structures after a basic volcanic event, i.e., the eruption in 1984. In [53,54], the P-velocity model was calculated using (1) sonic log data collected within K-18 and (2) P-wave data generated by the explosive source (2 km outside of K-18) and air gun (over K-18). The processing of data (1) showed that the average velocity of the acoustic P-wave is 4.43 km/s.…”
Section: Identification Of Well-resolved Seismic Anomaliessupporting
confidence: 77%
“…Thus, the profiling results [53,54], as well as our results, detected the state of subsurface velocity structures after a basic volcanic event, i.e., the eruption in 1984. In [53,54], the P-velocity model was calculated using (1) sonic log data collected within K-18 and (2) P-wave data generated by the explosive source (2 km outside of K-18) and air gun (over K-18). The processing of data (1) showed that the average velocity of the acoustic P-wave is 4.43 km/s.…”
Section: Identification Of Well-resolved Seismic Anomaliessupporting
confidence: 77%
“…on the surface. Further, the received signal is processed and a model near the well or interwell space is constructed [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…To date, attempts to analyze the geotemperature field of tunnels based on field investigations have made some progress [6][7][8][9][10]. As a pioneering definition, when the buried depth of the tunnel is too large, or the temperature of the surrounding rock affected by magmatic activity is more than 30 • C, this kind of tunnel is called a high geotemperature tunnel [11].…”
Section: Introductionmentioning
confidence: 99%